ANALISIS SEMIOTIKA BODY SHAMING DALAM FILM IMPERFECT - Julidar (SADIDA, 2022)
The film Imperfect: Career, Love, and scales is a form of criticism on the issue of body shaming in Indonesia. The purpose of this movie is to increase self-love and show respect for others by abstaining from making physical comparisons with them. Even in families, friendship groups, and places of employment, body shaming is frequently made fun of. Social media is also used to promote hate through body shaming. The objectives of this study are to ascertain the meaning of body shaming's denotation and connotation in the movie Imperfect and to ascertain the semiotic analysis of the Islamic viewpoint on body shaming in the movie Imperfect. Roland Barthes' semiotic analysis method, which looks at denotation and connotation, is used in this study's qualitative methodology. The body shaming in the film Imperfect is explained using Barthes' semiotic theory. The findings indicated that body shaming, both verbal and nonverbal, occurred in the movie Imperfect. In the movie Imperfect, verbal body shaming takes the form of disparaging body type, skin tone, and fashion choices made by others. Nonverbal behaviors including cynical looks, laughter, shocked looks at someone's bodily changes, and whispering are examples of body shaming. Body shaming that is practiced vocally and nonverbally is extremely reprehensible behavior if it is connected to an Islamic worldview.